Efficacy of Injected Corticosteroid Type, Dose, and Volume for Pain in Large Joints: A Narrative Review. Issue 7 (31st January 2018) - Cushman, Daniel M.; Bruno, Benjamin; Christiansen, Jacob; Schultz, Andrew; McCormick, Zachary L.
Abstract: Corticosteroid injections are commonly used in the treatment of disorders of the large joints. This review assimilates the available literature on corticosteroid injections into the glenohumeral joint, subacromial space, hip joint, and knee joint. A systematic method to review available literature revealed 84 articles that fit the inclusion criteria. For each injection location, four items were examined: overall efficacy of injection, superior type of steroid, superior dose of steroid, and superior volume of injectate. Most research demonstrates positive short‐term outcomes in pain and function for corticosteroid injections of the large joints. Methylprednisolone and triamcinolone seem similar in efficacy, with minor differences seen in specific studies. Larger doses may last longer, but need to be balanced with the systemic effects from higher doses. Volume has not been studied extensively. Due to heterogeneity in study types, subject populations, and outcomes, it is not possible to identify a single defining trend for a superior type, dose, or volume of steroid. Future prospective studies examining these factors may better reveal the optimum regimen for each injection location. Level of Evidence: III